Malaysian socio-demographic characteristics, mean haemoglobin levels and BMI distribution of the monthly transfused group (MTG) and non-monthly transfused group (NMTG) thalassemia patients - Mohammed Ibraheem, Shahad; Sathar, Jameela; Seman, Zainina; Khalid, Bahariah (Universidad Tecnica de Manabi, 2022)
Background: Thalassemia is a genetic blood disorder characterized by insufficient haemoglobin level due to mutation in the globin chains causing anaemia with iron overload and the most common genetic haemoglobinopathy in Malaysia. They are grouped as transfusion dependent and non-dependent according to their transfusion requirement. The frequency of thalassemia transfusions can be discriminated further into monthly to non-monthly transfusion group. Objective: To analyze the socio-demographic characteristic, haemoglobin levels and BMI distribution after classifying the thalassemia patients according to monthly transfused group (MTG), non-monthly transfused group (NMTG) and comparing to a healthy individual control group. Methods and Materials: This was a prospective cross-sectional study gathering data on socio-demographic characteristic, haemoglobin levels and BMI distribution of patients with MTG and NMTG thalassemia patients from a thalassemia clinic in Ampang Hospital and comparing them to healthy individuals in Faculty of Medicine and Health Sciences, Universiti Putra Malaysia. The study embarked between August to October 2020. Results: Our study clearly shows in adult thalassemia MTG are predominantly in Malay ethnicity and younger in comparison to NMTG. The mean Hb levels of MTG is lower compared to NMTG regardless of the genotype and phenotype characteristics.